A new species of Pristimantis (Anura: Strabomantidae) with a colourful venter from the cloud forests of Colombian western Andes - Palacios-Rodríguez, Pablo; Daza, Juan M.; Mazariegos-H., Luis A.; Rendón, Ubiel; Amézquita, Adolfo (Zootaxa, 2022)
The Terrarana frogs of the genus Pristimantis are acknowledged for their direct development into froglets and for their astonishing species richness, which renders it the anuran genus with the highest number of species. We describe a new species of Pristimantis from the northwestern Andes of Colombia. The species is distributed from an area between 2750-2900 m.a.s.l. in the Mesenia-Paramillo Nature Reserve. Pristimantis postducheminorum sp. nov. differs from other, phylogenetically related, or similar resembling Pristimantis taxa by a striking yellow coloration in the ventral area, dark grey coloration in the concealed surfaces of the thighs and groin, absence of nuptial pads, presence of lateral fringes on fingers, presence of vomerine odontophores triangular in shape from the ventral view, and absence of dorsolateral folds. Molecular phylogenetics place this new species close to P. satagius and therefore within the P. ridens species group. The new species is also phylogenetically close and sympatric with the recently described P. ferwerdai, which further indicates that the Pristimantis fauna has been notoriously underestimated in the Colombian western cloud forests, a fact that should be considered in assessments of environmental impact.